RECOVERY EXECUTION PLAN WASTE SOIL AT PT. ABC INDONESIA OPERATION AREA (The Indonesian Journal of Business Administration, 2021)
PT. ABC Indonesia (PT.ABC) has oil field under one of Indonesia PSC (Production Sharing Contract) where PT. ABC is as a contract operator of Government of Indonesia. Remediation activities have been going on for several years, with hundreds of sites having waste soil successfully clean up to obtaining a clean declaration letter from Government of Indonesia. A field verification review was carried out by identifying several sites that were very difficult to complete considering the very complex process from the beginning to the remediation activities. Government of Indonesia asked PT. ABC to seeks things that can be done before the end of concession period and develop a good execution plan that can be done by PT. ABC as well for the next operator. By carrying out very good discussions and brainstorming to the main leads in line with the objectives of PT. ABC and Government of Indonesia, and taking into account the critical factors in making the execution plan, can determine the best alternative from the criteria to align with all stakeholder. Continuing to submit the remediation plan along with continuing delineation and land access efforts, and carrying out surface removal is the best solution for this execution plan.Keywords: Analytical Hierarchy Process (AHP), Critical Factors, Execution Plan, Standard Remediation Process